THE EFFECTIVENESS OF USING TOURISM BROCHURESIN TEACHING WRITING DESCRIPTIVE TEXT:AN EXPERIMENTAL STUDY IN THE THIRD GRADE OF JUNIOR HIGH SCHOOL - Runi Ekaningtias, - (2007)
The study is entitled The Effectiveness of Using Tourism Brochures in Teaching Writing Descriptive Text. This research is to find out the effectiveness of using tourism brochures in teaching writing descriptive text in junior high school. This study was conducted by using experimental method in which the data were collected by administering pre-test and post test to the experimental and control group. The third grade students of MTs. Assalafiyah Assirojiyah Cikalongkulon Cianjur (IX-A and IX-B) were involved in this inquiry. The data were gathered from 27th of October 2006 to 9th of December 2006. The result indicates that generally both classes performed better achievement on their writing ability, but the experimental students gained higher writing achievement than those of the control students. It means that students of tourism brochures group significantly performed better writing ability than those in non-tourism brochures group. These findings can be adopted as a promising considerable alternative in teaching writing to junior high school students. English teachers can modify and improve their teaching media in the hope that the students' writing ability will be improved.